PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS APLIKASI POWTOON TERHADAP MINAT BELAJAR SISWA KELAS IV SD NEGERI RETRAEN PADA MATERI SISTEM TATA SURYA - Mbuik, Heryon Bernard; Maria Mesti Bani; Florida Am’isa; Anjes Umbu Landu; Ayu Stefania Savitri Kehi; Eltiana Odes; Metriana Tae; Resti Rosmalinda Batmaro; Yufri Supriadi Manilaka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effect of Powtoon-based digital media on fourth-grade students' learning interest in the Solar System topic at SD Negeri Retraen. The research employed a quasi-experimental design with a nonequivalent control group. Participants were divided into two groups: the experimental group, which used Powtoon animation media, and the control group, which received conventional instruction. Learning interest was measured through a Likert-scale questionnaire covering attention, curiosity, participation, and enthusiasm. Data were analyzed using an independent sample t-test. The results indicated that the experimental group achieved significantly higher post-test scores in learning interest compared to the control group, as evidenced by a p-value below 0.05. These findings suggest that integrating Powtoon animation media into thematic instruction effectively enhances student engagement, particularly in abstract science topics such as the Solar System. The dynamic visualization provided by Powtoon helps students comprehend complex material more concretely, fostering a more interactive and enjoyable learning experience. This study recommends the broader adoption of digital animation tools in elementary education to improve instructional quality and increase student participation.